RECONSTRUCTING CONTRACT LAW: ADDRESSING INEQUALITIES AND ETHICAL CHALLENGES IN MODERN COMMERCIAL TRANSACTIONS - Zulkifli; Muhibuddin; Rahmaniar; Nasrianti; Sofyan Jafar (PT. Radja Intercontinental Publishing, 2024)
The rapid expansion of digital platforms in Indonesia has reshaped its economy, with e-commerce transactions expected to reach IDR 487.01 trillion in 2024, positioning Indonesia as a major player in Southeast Asia's digital economy (Google, Temasek, & Bain, 2023). Despite the advancements, the platform economy has introduced significant inequalities between platform operators and consumers, leading to consumer exploitation through data manipulation, dynamic pricing algorithms, and unclear contract terms. These issues are further exacerbated by Indonesia’s existing legal framework, which struggles to address the challenges posed by digital transactions. This study critically evaluates Indonesia's consumer protection laws and identifies the gaps allowing these exploitative practices. It proposes a legal reconstruction model that focuses on ensuring transparency, fairness, and accountability in digital contracts. The study's key findings highlight the legal deficiencies in regulating platform monopolies, the need for clearer regulations on algorithmic pricing, and the underregulation of data privacy concerns. Recommendations for legal reform aim to enhance consumer protection, creating a more equitable digital economy.